Kinetic Study on Adsorption of Monoethanolamine (MEA) Wastewater Treatment Using Activated Carbon, Chitosan and Rice Husk via Batch Process - Mohd Najib, Razali; Siti Zulaikha, Isa (2014)
In petrochemical industry, monoethanolamine (MEA) is a common solvent used as absorption medium to remove carbon dioxide (CO2) from gaseous stream. In the absorber the reaction between CO2 and MEA will generate some salt and increased the amount of the suspended solids in an absorber due to direct contact between gas and liquid (two fluid phases)